Praktikum za dedno pravo - Kraljić, Suzana; Drnovšek, Katja (University of Maribor Press, 2024)
Practicum for Succession Law. Succession law, as one of the fundamental areas of legal studies, plays a crucial role in regulating the transfer of assets and rights from a deceased person to others. The Practicum for Succession Law will serve as an invaluable source of knowledge and practical experience. It is primarily intended for students of the Faculty of Law at the University of Maribor, but also for anyone who wishes to understand or deepen their knowledge of succession law and tackle the challenges that may arise in the process of succession.